Art what is itn why is itn - Canaday, John Edwin 1907-. (Chicago Encyclopedia Britannica Films, 1962)
John Canaday analyzes the place of art among the humanities, as an expression of man's attempt to define what it means to be a human being. The program shows how the masterworks of art and architecture have formed a visual history of man's thought, ideals, and most widely held beliefs.
VCD 2.0
Produced and directed by John Barnes.
Narrated by Donald Moffat.
Keywords: Architecture and history; Art and society; Architecture and society; Art and history